2006
DOI: 10.1021/jo061436l
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-Catalyzed 1,3-Isomerization of Allylic Alcohols: Scope and Chirality Transfer

Abstract: The scope of the triphenylsilyl perrhennate (O3ReOSiPh3, 1) catalyzed 1,3-isomerization of allylic alcohols has been thoroughly explored. It was found to be effective for a wide variety of secondary and tertiary allylic alcohol substrates bearing aryl, alkyl, and cyano substituents. Two general reaction types were found which gave high levels of product selectivity:  those driven by formation of an extended conjugated system and those driven by selective silylation of a particular isomer. The efficiency of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 65 publications
1
31
0
1
Order By: Relevance
“…(E)-3-(2-Nitrophenyl)prop-2-en-1-ol: [18,36] (E)-3-(3-Nitrophenyl)prop-2-en-1-ol: [37] 97 %. (E)-3-(4-Nitrophenyl)prop-2-en-1-ol: [18,39] 98 %.…”
Section: Methodsunclassified
“…(E)-3-(2-Nitrophenyl)prop-2-en-1-ol: [18,36] (E)-3-(3-Nitrophenyl)prop-2-en-1-ol: [37] 97 %. (E)-3-(4-Nitrophenyl)prop-2-en-1-ol: [18,39] 98 %.…”
Section: Methodsunclassified
“…In some cases, the use of acyl donors with a longer alkyl chain, such as vinyl butyrate and vinyl decanoate, produced higher enantioselectivities (entries 5- 7, 9, 13, and 14). Moreover, it was applicable to benzyl 1 q, furyl 1 r, and propargyl alcohols 1 s to give 3 q-s in excellent yield and enantioselectivity, whereas the previous conditions using 4 or 5 [6] were relatively ineffective (entries [17][18][19]. Optically pure (R)-3 n, the key synthetic intermediate of (+)-tanikolide, which employed the less expensive cyclohexenone as the starting material, was produced in twice the previously obtained yield (entry 14).…”
mentioning
confidence: 99%
“…Grubbs studied Osborn's reaction and found that O 3 ReOSiPh 3 isomerizes allylic alcohols stereospecifically 3. Both Osborn and Grubbs invoked a concerted [3,3] rearrangement of allylic perrhenate esters to explain this very facile and selective isomerization (Figure 1).…”
mentioning
confidence: 99%
“…Osborn proposed an ionic mechanism to explain the kinetics for formation of Z -alkenes,2b and Grubbs invoked a similar mechanism to explain the loss of optical purity with certain electron-rich allylic alcohol substrates (Figure 1). 3 The proposed ionic mechanism attracted our attention because it suggested that Re(VII) complexes might activate and solvolyze electron rich alcohols. We report herein a Prins cyclization initiated by Re(VII) catalysts4 based on this concept that is both very mild and shows unusual selectivity.…”
mentioning
confidence: 99%